Pyrosequencing Analysis of Salinomycin and Eimeria spp. Challenge-Induced Changes in Broiler Cecal Microbial Communities - Kley , A. Martynova-Van; Manoharan, M.S.; Bray, J.; Hume, M.E.; Dowd, S.E.; Nalian, A. (International Journal of Poultry Science, 2013)
Eimeria spp. invade and damage the intestinal cell lining of broilers resulting in cell necrosis and secondary bacterial infections. The current work investigates the effect of anticoccidial agents, salinomycin in combination with Roxarsone and Eimeria-challenge on the composition of broiler cecal microflora. Three hundred and twenty day-old male Cobb broilers were among four treatment groups: NN (no salinomycin and no Eimeria challenge) and NC (no salinomycin plus Eimeria challenge) received basal diet with no salinomycin, while SN (salinomycin and no Eimeria challenge) and SC (salinomycin plus Eimeria challenge) received basal diet with salinomucin. Broilers in groups NC and SC were orally gavaged on d 28 with a mixed Eimeria spp. challenge. Body weight and Eimeria lesion scores were determined at d 35. Cecal bacterial DNA from broilers at day 28 and day 35 were subjected to 454 pyrosequencing of 16S rDNA for sequence identification. Relative percent abundance and richness of the identified taxa were analyzed. Salinomycin had significant influence on the total number of taxa (p = 0.02) and on cecal microbial community structure (p = 0.002). The mixed Eimeria challenge marginally affected the total number of taxa (p = 0.06) and the composition of microbial communities (p = 0.09). Broiler age, body weight and Eimeria lesion score had no significant effect on the cecal microbial communities. Results from this study indicate that pyrosequencing is effective in understanding the dynamics and functionality of cecal microbial communities in relation to anticoccidial treatment, Eimeria challenge and broiler performances.